2001
DOI: 10.1016/s0034-6667(01)00051-3
|View full text |Cite
|
Sign up to set email alerts
|

Archaeopteris from the Upper Famennian of Belgium: heterospory, nomenclature, and palaeobiogeography

Abstract: New fertile specimens of Archaeopteris roemeriana from Upper (but not uppermost) Famennian strata of Belgium have been studied. Crowded sporangia are borne on non-laminate, three times bifurcate fertile leaves helically arranged around the fertile ultimate axes. Vegetative leaves occur both proximal and distal to the fertile leaves. Heterospory is demonstrated with miospores belonging to the Geminospora-Aneurospora complex and macrospores most probably to Contagisporites genus. The established morphological tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…halliana is presently unknown. Kräusel & Weyland (1941) and Fairon‐Demaret et al (2001) proposed that these two species are synonymous. In addition, A .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…halliana is presently unknown. Kräusel & Weyland (1941) and Fairon‐Demaret et al (2001) proposed that these two species are synonymous. In addition, A .…”
Section: Discussionmentioning
confidence: 99%
“…roemeriana ) are characterized by laminated and non‐laminated fertile leaves, respectively. Fairon‐Demaret et al (2001) suggested that their different leaf shapes mainly correlate with distinct biotopes, that is, non‐laminated fertile leaves of A . roemeriana may be more efficient for wind dispersal of spores and for good control of water loss by transpiration; this reproductive organ may help better cope with dry and stressful periods of a lower water table in the Late Famennian.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations